The practice of Cousin Marriage in the Community of Kalola Village, Pasangkayu Regency, West Sulawesi - Muhammd Rizal Soulisa; Lukman S. Thahir; Malkan Malkan (State Institute for Islamic Studies Palu, 2020)
The aim of this paper is to discuss the practice of cousin marriage in the community of Kalola Village, Pasangkayu Regency, West Sulawesi. This study uses qualitative methods and data was gathered through observation, in-depth interviews, and written material. Data analysis was analyzed using grounded theory approach. the background of a cousin marriage in the Mandar tribe community in Kalola Village is a tradition that has been strong for a long time in the community, in addition to the factor of maintaining a large family and protecting property. Meanwhile, the impact of cousin marriage includes both positive and negative impacts. The positive impact is to reduce the number of conflicts in the community and strengthen local political systems, while the negative impact is the breakdown of kinship in the event of conflict and divorce and health risks.